Contribuições da cartografia temática como instrumento analítico em estudos históricos. - José Rogério Beier; Lucas Montalvão Rabelo (Confins)
This paper aims to highlight the potential contribution of the Thematic Cartography to historical studies as an analytical tool of the documentation raised during the research. To do so, the article will begin with a brief introduction about Thematic Cartography and its main methodological aspects, and then to present two examples of its use in academic investigations in the History field. It is sought, therefore, to draw attention to some relevant elements of this tool that can serve the historian in the formulation of new problems for his investigation; in the analysis of the problems already formulated and, mainly, in the construction of the argumentation of his narrative. In the end, it is intended to point out the importance of the use of this instrument in the historical studies, once it is associated with the questions and problems of the research, and not merely for aesthetic or technical reasons.